Matrix-Assisted Laser Desorption/Ionization Time-of-Flight Mass Spectrometry Combined with Magnetic Beads for Detecting Serum Protein Biomarkers in Parkinson’s Disease - Li, Yao-Hua; Wang, Jian; Zheng, Xiao-Li; Zhang, Yan-Li; Li, Xin; Yu, Shun; He, Xin; Chan, Piu (European neurology, 2011)
Background: Biomarkers for neurodegenerative diseases are essential to facilitate disease diagnosis. Application of proteomics has greatly hastened the search for novel biomarkers. In this study, new potential biomarkers were discovered, and a diagnostic pattern was established for idiopathic Parkinson’s disease (PD) by using proteomic technology. Methods: Serum proteins from PD patients and controls were captured by magnetic bead-based weak cation exchange. The molecular weight of the proteins in bead-binding fraction was detected by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF-MS). Biomarker Wizard 3.1 and Biomarker Patterns Software were used for data analysis and constructing a model of biomarkers. A blinded testing set was used to validate the model. Results: A total of 17 discriminating m/z peaks related to PD were identified. The model based on the 5 biomarkers generated an excellent separation between PD and healthy controls with 98.36% for the sensitivity and 83.05% for the specificity. Blind test data demonstrated the model could recognize patients with PD with a sensitivity of 85.0% and a specificity of 70.0%. Conclusions: The preliminary data suggested a potential application of MALDI-TOF-MS combined with magnetic beads. The model comprising 5 promising biomarkers can differentiate individuals with PD and the healthy subjects precisely.